29.6k views
0 votes
I really need help with this one

I really need help with this one-example-1
User Roberto
by
4.7k points

1 Answer

5 votes

Answer:

7 (z - 2)

= ----------------

4 (z + 1)

Explanation:

7z^2 + 7z z^2 - 4

---------------- · -----------------------

4z + 8 z^3 + 2z^2 + z

7z(z + 1) (z + 2)(z - 2)

= ---------------- · -----------------------

4(z + 2) z(z^2 + 2z + 1)

7z(z + 1) (z + 2)(z - 2)

= ---------------- · -----------------------

4(z + 2) z(z + 1)(z + 1)

7 (z - 2)

= ----------------

4 (z + 1)

User Lbonn
by
4.8k points